The effect of artificial side wind on the serve ofcompetitive tennis players - Mendes, C. Pedro (2012)
In tennis, the serve is the shot ofgreatest importance.The servedependsmainly on the player’stechnique, however,environmental factorscan influencethe accuracy of the serve. This study highlights the effect of side wind on the serve of 12 experienced tennis players. The players were asked to hit the intersection point betweenthe centralandthe service line at maximum speed while awind effect was artificially generated by a ventilator setup with various speed of Induced Aerodynamic Flow (IAF).Each player’s serve was then analyzed using error ellipsesas a statistical measure. Thismethod allowed us toevaluate theeffect of "random wind"in comparison to“constant wind” on the accuracy of the serves.The truncated Fourier series analysis showedthat there was an adaptive pattern in the accuracy of the serve dependingon therandom wind. However in four players,the more unpredictablethe impact of the wind the more accurate they becamewith the serve. The fact that there was not a linear trend in the accuracy of serveswhen IAFincreased shows that each playeradapts differentlytothe windinfluence.